Helium Ion Microscopy Visualizes Lipid Nanodomains in Mammalian Cells. Issue 43 (5th October 2015) - Schürmann, Matthias; Frese, Natalie; Beyer, André; Heimann, Peter; Widera, Darius; Mönkemöller, Viola; Huser, Thomas; Kaltschmidt, Barbara; Kaltschmidt, Christian; Gölzhäuser, Armin
Abstract : Cell membranes are composed of 2D bilayers of amphipathic lipids, which allow a lateral movement of the respective membrane components. These components are arranged in an inhomogeneous manner as transient micro‐ and nanodomains, which are believed to be crucially involved in the regulation of signal transduction pathways in mammalian cells. Because of their small size (diameter 10–200 nm), membrane nanodomains cannot be directly imaged using conventional light microscopy. Here, direct visualization of cell membrane nanodomains by helium ion microscopy (HIM) is presented. It is shown that HIM is capable to image biological specimens without any conductive coating and that HIM images clearly allow the identification of nanodomains in the ultrastructure of membranes with 1.5 nm resolution. The shape of these nanodomains is preserved by fixation of the surrounding unsaturated fatty acids while saturated fatty acids inside the nanodomains are selectively removed. Atomic force microscopy, fluorescence microscopy, 3D structured illumination microscopy, and direct stochastic optical reconstruction microscopy provide additional evidence that the structures in the HIM images of cell membranes originate from membrane nanodomains. The nanodomains observed by HIM have an average diameter of 20 nm and are densely arranged with a minimal nearest neighbor distance of ≈15 nm. Abstract : Helium ion microscopy is capable of imaging biological specimens without any conductive coating, and it allows the identification of nanodomains in the ultrastructure of membranes with 1.5 nm resolution. The shape of these nanodomains is preserved by fixation of the surrounding unsaturated fatty acids, while saturated fatty acids inside the nanodomains are selectively removed.